Reação de pessegueiros a Monilinia fructicola (wint.) Honey e sua relação com componentes bioquímicos - Fabiane, Keli Cristina (2011)
The brown rot caused by the fungus Monilinia fructicola (Wint.) Honey, is the main disease in stone fruit trees (Prunus spp.). It can be found in almost all fruit orchards, causing severe losses to fruit growers. The main symptoms of this disease are the blossom blight, twig cankers and necrosis and, fruits rot. Thus, the economic losses of brown rot may occur since flowering, extending to the pre-and post-harvest fruit phases. The aim of this study were (i) to test the brown rot reaction of different peach genotypes, identifying the resistant or tolerant ones to brown rot on flowers, (ii) to identify resistance and/or tolerance sources to this fruit disease and (iii) to identify resistance mechanisms associated with the physical, chemical and biochemical characteristics in peach fruits, iv) to identify superior genotypes for biochemical characteristics; v) to study the genetic divergence of peach genotypes on the UTFPR collection. The work was carried out at Laboratório de Fitossanidade, Universidade Tecnológica Federal do Paraná (UTFPR) – Campi Dois Vizinhos and Pato Branco, in the 2009/2010 and 2010/2011 production cycles. The genotypes analyzed were the peach collection of the UTFPR, in Pato Branco, PR. Five and 16 genotypes were tested in the first and second cycles, respectively, in relation for flowers brown rot reaction. For fruit disease reaction 26 and 29 peach genotypes were tested in the production cycles 2009/2010 and 2010/2011, respectively. The tests aimed to evaluate the flower incidence and the fruits incidence and severity, after pathogen inoculation. The physical-chemical and biochemical fruit characteristic, and were evaluated as well as their relation if any with epidemiological variables. Genotypes were also determined by biochemical fruit characteristics. The genetic divergence among peach genotypes for epidemiological variables and biochemical fruit characteristics was also studied. Different levels of susceptibility to blossom blight were obtained, being the 'Cascata 1070' and 'Cascata 1055' the ones with lowest susceptibility, demonstrating potential for use in orchards or as parents in future breeding programs. The 'Tropic Beauty', 'Cascata 962', 'Conserva 1187', 'Kampai', 'Cascata 1063', 'Tropic Snow' and 'Rubimel' peach genotypes showed the lowest incidence and severity for brown rot in the 2009/2010 and 2010/2011 cycles, which indicates them as disease possible tolerant. There was no correlation between the blossom blight incidence percentage and the brown rot fruit incidence and severity. There were correlation between TSS, pH, reducing sugars, total amino acid content and PAL enzyme for brown rot reaction.